Sustainable development of ecological environment in resource-based cities in Heilongjiang Province - Sun Lu (E3S Web of Conferences, 2020)
Based on the specific situation of ecological environment of resource-based cities in Heilongjiang Province, this paper puts forward the development goal and key points of sustainable development of ecological environment, and puts forward the guarantee measures of sustainable development of ecological environment of resource-based cities from three levels of government, enterprise and the public.